RNF213 Variant and Infectious Burden Associated With Intracranial Artery Stenosis in Moyamoya Disease - Chaofan Zeng; Peicong Ge; Zihan Yin; Junlin Lu; Xiaofan Yu; Junsheng Li; Yuanren Zhai; Chenglong Liu; Qiheng He; Wei Liu; Jia Wang; Xingju Liu; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background The mechanisms driving the progression of moyamoya disease (MMD) remain unrecognized. There is evidence suggesting that genetic and environmental factors may be associated with intracranial artery stenosis. Here, we aimed to investigate the characteristics of infectious exposure and the association of the RNF213 (RING finger protein 213) variant and infectious burden (IB) with intracranial artery stenosis of MMD. Methods and Results We prospectively recruited 275 patients with MMD. Participants underwent RNF213p.R4810K sequencing. Serum antibody titers of herpes simplex virus, cytomegalovirus, toxoplasma, rubella virus, and Epstein‐Barr virus were assessed and combined into an IB score. The degree of intracranial artery stenosis was measured by using the Willis narrowing score (WNS), which was then dichotomized as mild and severe. Multivariate regression analyses were performed to analyze variables associated with severe WNS. Patients with the RNF213 variant had a higher risk of severe WNS than wild‐type individuals (P=0.003). Patients with MMD with severe WNS showed an increased level of IB score (P<0.001). The RNF213 variant (odds ratio [OR], 2.832 [95% CI, 1.347–5.955]; P=0.006) and IB score (OR, 1.771 [95% CI, 1.286–2.439]; P<0.001) were significantly associated with severe WNS after adjusting for covariates. Furthermore, the associations between IB score and severe WNS were more prominent among patients with modifiable risk factors of elevated body mass index (Pinteraction<0.001), triglycerides (Pinteraction=0.011), and homocysteine (Pinteraction=0.016). Conclusions This study outlined a perspective of the genetic‐environmental interactions in the progression of MMD. The RNF213 variant and increased IB were associated with intracranial artery stenosis in MMD. The study will provide novel insights into the mechanism of disease progression, which may offer opportunities for early intervention of infectious exposure in MMD.